Stemming the Tide: What Have EU Countries Done to Support Low-Wage Workers in an Era of Downward Wage Pressures? - Sarah Marchal; Ive Marx (Institute for the Study of Labor (IZA), 2015)
Governments across the EU have been striving to get more people into work while at the same time acknowledging that more needs to be done to 'make work pay'. Yet this drive comes at a time when structural economic shifts are putting pressure on wages, especially of less skilled workers. This article focuses on trends in minimum wages, income taxes, and work-related benefits within a selection of 16 EU countries, for the period 2001-2012, with three US states included as reference cases. We find evidence for eroding relative minimum wages in various EU countries, yet combined with catch-up growth in the new Member States. We also find that governments counteracted eroding minimum wages through direct income support measures, especially for lone parents. Most prevalent among these were substantial declines in income tax liabilities. More generally we see a trend unfolding towards a fiscalization of income support policies.
Keywords: I38; 330; minimum wage; income support; fiscalization; lone parents